Evaluation Methods and Progress of Right Ventricular-pulmonary Artery Coupling - Xinqi Wang, MS, Anni Chen, MS, Lan Yang, MS, Ya Chen, MS, Zhenyi Li, MS, Zhaojun Li, MD, Lin Jin, MD (Advanced Ultrasound in Diagnosis and Therapy)
Right ventricular-pulmonary artery coupling (RV-PAC) serves as an indicator of the efficiency of energy transfer from the right ventricle to the pulmonary circulation. It plays a critical role in the diagnosis, clinical treatment, and prognosis of conditions such as pulmonary hypertension, heart valve disease, and heart failure. Various non-invasive evaluation methods have recently been proposed for assessing RV contractility and arterial afterload, based on the end-systolic elastance to arterial elastance ratio (Ees/Ea), which is derived from invasive pressure-volume loops. In this review, we summarize the fundamental concepts, physiological mechanisms, examination methods, influencing factors, and clinical significance of RV-PAC to provide a valuable reference for clinical practice.